RANCANG BANGUN APLIKASI PKM (PROGRAM KREATIVITAS MAHASISWA) DI UNIVERSITAS LAMPUNG MENGGUNAKAN METODE RUP (RATIONAL UNIFIED PROCES) PADA FCM (FIREBASE CLOUD MESSAGING) ANDROID DAN SMS GATEWAY - Qonitati Qonitati; Astria Hijriani; Rico Andrian (Universitas Lampung, 2018)
PKM (Student Creativity Program) is a program of Directorate of Research to improve the quality of students. PKM at the University of Lampung already exists and the participants continue to increase for each year. Information related to the implementation of PKM at the University of Lampung has also been submitted by the BAK (Bureau of Academic and Student Affairs) University of Lampung through the website, but according to the BAK that students are less active in visiting the website. Applications that can provide reminders related to PKM information can help students to obtain PKM information. PKM application that can provide this reminder is developed using FCM (Firebase Cloud Messaging) and sms gateway. FCM serves to provide android notifications. PKM application is also developed using RUP (Rational Unified Process) with 4 phases of inception, elaboration, construction and Transition. Inception is business modeling and requirement, then in elaboration phase is analysis, design and implementation. The processes performed in the construction phase are testing, analysis, design and implementation, while the process in the transition phase is testing and deployment. Tests conducted in this study using black box testing with a success rate of 88%.Keywords: android; education; fcm, gammu; mysql; php; pkm; sms gateway; university of lampung.